Epidemiological pattern of COVID-19 and its association with periodontal health in an urban Indian cohort - Gupta, Ishita; Patel, Shivani A.; Kondal, Dimple; Goodman, Michael; Mohan, Sailesh; Ali, Mohammed K.; Tandon, Nikhil; Narayan, K. M. Venkat; Prabhakaran, Dorairaj; Shridhar, Krithiga (Frontiers in Public Health, 2023)
Background Studies have highlighted a possible influence of gingival and periodontal disease (PD) on COVID-19 risk and severity. However, the evidence is based on hospital-based studies and community-level data are sparse. Objectives We described the epidemiological pattern of SARS-CoV-2 infection in Delhi and evaluated the associations of gingival and PD with incident COVID-19 disease in a regionally representative urban Indian population. Methods In a prospective study nested within the Centre for Cardiometabolic Risk Reduction in South-Asia (CARRS) study, participants with clinical gingival and periodontal status available at baseline (2014–16) (n = 1,727) were approached between October 2021 to March 2022. Information on COVID-19 incidence, testing, management, severity was collected as per the WHO case criteria along with COVID-19 vaccination status. Absolute incidence of COVID-19 disease was computed by age, sex, and oral health. Differences in rates were tested using log-rank test. Poisson regression models were used to evaluate independent associations between gingival and PD and incidence of COVID-19, adjusted for socio-demographic and behavioral factors, presence of comorbidity, and medication use. Results Among 1,727 participants, the mean age was 44.0 years, 45.7% were men, 84.5% participants had baseline gingival or PD and 89.4% participants had received at least one dose of COVID-19 vaccine. Overall, 35% (n = 606) participants were tested for COVID-19 and 24% (n = 146/606) tested positive. As per the WHO criteria total number of cases was 210, constituting 12% of the total population. The age and sex-specific rates of COVID-19 were higher among men and older participants, but women aged >60 years had higher rates than men of same age. The incidence rate did not differ significantly between those having gingival or PD and healthy periodontium (19.1 vs. 16.5/1,000 person-years) and there was no difference in risk of COVID-19 by baseline oral disease status. Conclusion Gingival and PD were not associated with increased risk of COVID-19.